Annealing High Aspect Ratio Microgels into Macroporous 3D Scaffolds Allows for Higher Porosities and Effective Cell Migration. Issue 24 (9th October 2022) - Suturin, Alisa C.; Krüger, Andreas J. D.; Neidig, Kathrin; Klos, Nina; Dolfen, Nina; Bund, Michelle; Gronemann, Till; Sebers, Rebecca; Manukanc, Anna; Yazdani, Ghazaleh; Kittel, Yonca; Rommel, Dirk; et al.
Abstract: Growing millimeter‐scaled functional tissue remains a major challenge in the field of tissue engineering. Therefore, microporous annealed particles (MAPs) are emerging as promising porous biomaterials that are formed by assembly of microgel building blocks. To further vary the pore size and increase overall MAP porosity of mechanically stable scaffolds, rod‐shaped microgels with high aspect ratios up to 20 are chemically interlinked into highly porous scaffolds. Polyethylene glycol based microgels (width 10 µm, lengths up to 200 µm) are produced via in‐mold polymerization and covalently interlinked into stable 3D scaffolds via epoxy‐amine chemistry. For the first time, MAP porosities can be enhanced by increasing the microgel aspect ratio (mean pore sizes ranging from 39 to 82 µm, porosities from 65 to 90%). These porosities are significantly higher compared to constructs made from spherical or lower aspect ratio rod‐shaped microgels. Rapid filling of the pores by either murine or primary human fibroblasts is ensured as cells migrate and grow extensively into these scaffolds. Overall, this study demonstrates that highly porous, stable macroporous hydrogels can be achieved with a very low partial volume of synthetic, high aspect ratio microgels, leading to large empty volumes available for cell ingrowth and cell–cell interactions. Abstract : Rod‐shaped microgels with high aspect ratios (5–20) are produced via in‐mold copolymerization of polyethylene glycol diacrylate and 2‐aminoethylmethacrylate, and subsequently annealed into macroporous scaffolds using an epoxy‐functionalized interlinking agent. The higher microgel aspect ratios lead to porosities up to 90% and mean pore sizes up to 82 µm, while supporting rapid, extensive filling of the constructs by fibroblasts.